EKSPLORASI KEMAMPUAN SISWA KELAS IV SEKOLAH DASAR DALAM PENYELESAIAN SOAL CERITA MATEMATIKA - Ariawan, Vina Anggia Nastitie; Pratiwi, Inne Marthyanne (JPI (Jurnal Pendidikan Indonesia), 2017)
The objectives for this research are (1) to explore student’s strategies to solve story problem about measurement material; (2) to explore student’s learning difficulties to solve story problem. Subject of this research were 18 of fourth grade students of SDN Winduhaji in Kuningan subdisctrict. This research using qualitative approach within case study method. Data in this research using qualitative namely result of story problem. Techniques of collecting data in this research are using test, interview, and document analysis. Data analyzed by using thematic analisys meanwhile data validated by using triangulation, member checking, and reflectivity. The results of this research show that student’s strategies to solve story problem are (1) using pictures; (2) using diagram; (3) typed problem using addition, reduction, multiplication, and dividing operation. Student’s learning difficulties to solve problem story are (1) problem comprehension difficulties; (2) difficult to representation the problem conductes math and pictures; (c) concept comprehension difficulties; (d) difficult to develop solving strategies; (e) student’s cognitive disruption.